Johnson & Johnson's strategy with Motrin : the growing pains of social media - Eisele, Kathryn; Fishburne, Patrick; O'Rourke, James S., 1946- (London : SAGE Publications Ltd, 2017)
Johnson & Johnson experienced the rapid spread of negative backlash through social media channels in response to an online Motrin advertisement. The incident raises a discussion on the opportunities and risks of using social media in marketing and communications outreach, as well as how social media efforts should align with the companys overall business objectives.
Originally published: Eisele, K., Fishburne, P., & ORourke, J. S. (2010). Johnson & Johnsons strategy with Motrin: The growing pains of social media. 10-10. Notre Dame, IN: The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Johnson & Johnson Consumer Products; Pharmaceutical industry -- Marketing; Social media -- Economic aspects; Internet marketing